Language, Memory, and Mental Time Travel: An Evolutionary Perspective - Corballis, Michael C. (Frontiers in Human Neuroscience, 2019)
Language could not exist without memory, in all its forms: working memory for sequential production and understanding, implicit memory for grammatical rules, semantic memory for knowledge, and episodic memory for communicating personal experience. Episodic memory is part of a more general capacity for mental travel both forward and backward in time, and even into fantasy and stories. I argue that the generativity of mental time travel underlies the generativity of language itself, and could be the basis of what Chomsky calls I-language, or universal grammar, a capacity for recursive thought independent of communicative language itself. Whereas Chomsky proposed that I-language evolved in a single step well after the emergence of Homo sapiens, I suggest that generative imagination, extended in space and time, has a long evolutionary history, and that it was the capacity to share internal thoughts, rather than the nature of the thoughts themselves, that more clearly distinguishes humans from other species.